Bioinspired Highly Anisotropic, Ultrastrong and Stiff, and Osteoconductive Mineralized Wood Hydrogel Composites for Bone Repair. (6th March 2021) - Wang, Xiaofei; Fang, Ju; Zhu, Weiwei; Zhong, Chuanxin; Ye, Dongdong; Zhu, Mingyu; Lu, Xiong; Zhao, Yusheng; Ren, Fuzeng
Abstract: Anisotropic hydrogels mimicking the biological tissues with directional functions play essential roles in damage‐tolerance, cell guidance and mass transport. However, conventional synthetic hydrogels often have an isotropic network structure, insufficient mechanical properties and lack of osteoconductivity, which greatly limit their applications for bone repair. Herein, inspired by natural bone and wood, a biomimetic strategy is presented to fabricate highly anisotropic, ultrastrong and stiff, and osteoconductive hydrogel composites via impregnation of biocompatible hydrogels into the delignified wood followed by in situ mineralization of hydroxyapatite (HAp) nanocrystals. The well‐aligned cellulose nanofibrils endow the composites with highly anisotropic structural and mechanical properties. The strong intermolecular bonds of the aligned cellulose fibrils and hydrogel/wood interaction, and the reinforcing nanofillers of HAp enable the composites remarkable tensile strength of 67.8 MPa and elastic modulus of 670 MPa, three orders of magnitude higher than those of conventional alginate hydrogels. More importantly, the biocompatible hydrogel together with aligned HAp nanocrystals could effectively promote osteogenic differentiation in vitro and induce bone formation in vivo. The bone ingrowth into the hydrogel composite scaffold also yields good osteointegration. This study provides a low‐cost, eco‐friendly, feasible, and scalable approach for fabricating anisotropic, strong, stiff, hydrophilic, and osteoconductive hydrogel composites for bone repair. Abstract : Inspired by the hierarchical anisotropic structure of natural bone and wood, a low‐cost, eco‐friendly, feasible, scalable, and biomimetic "wood to bone" strategy is developed to fabricate highly anisotropic, ultrastrong and stiff, and osteoconductive mineralized wood hydrogel composites via impregnation of the alginate hydrogels into the microchannels of delignified wood followed by in situ mineralization of hydroxyapatite nanocrystals.